PELATIHAN SISTEM TEKNOLOGI CERDAS KETERSEDIAAN NUTRISI HIDROPONIK DAN TEKNIK BRANDING PRODUK PADA PEMBUDIDAYA HIDROPONIK KABUPATEN MAJENE - Sanjaya, Muhammad Fahyu; Kalsum, Ummu; Rosman, Andi (Jurnal Abdi Insani, 2025)
C Majene Regency is characterized by marginal land conditions, predominantly composed of rocky terrain, which limits the effectiveness of soil-based crop production in increasing vegetable availability. Hydroponic cultivation is one solution to address the availability of vegetables for the community. However, a consistent challenge in hydroponic farming is maintaining the quality and productivity of the plants. Additionally, the role of packaging as a branding tool in hydroponic businesses is often underutilized, reducing the appeal of the products generated by the hydroponic system. This training aims to enhance the knowledge and skills of the Unsulbar Farming Club (UFC) partners in using intelligent technology systems and product branding techniques to ensure the quality of crops produced through hydroponic systems. The methods employed in this training include lectures, demonstrations, discussions, and activity evaluations, involving 9 UFC partner participants. The activity results indicated an improvement in the knowledge and skills of Unsulbar Farming Club (UFC) partners regarding intelligent technology and product branding techniques, leading to an increase in sales scale for hydroponically grown plants.